National and Organizational Culture - Pavlova, Sanja; Krliu, Venera; Bojadjiev, Marjan (Business Management and Strategy, 2024)
The purpose of this paper is to show the importance of a culture which should be nurtured every day in all companies. Here, is also explained the meaning of organizational culture and national culture. As well as the connection between these two inseparable parts when it comes to different companies especially if talking about different countries and nations.